2016
DOI: 10.1371/journal.ppat.1005654
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons Direct Gammaherpesvirus Host Colonization

Abstract: Gamma-herpesviruses colonise lymphocytes. Murid Herpesvirus-4 (MuHV-4) infects B cells via epithelial to myeloid to lymphoid transfer. This indirect route entails exposure to host defences, and type I interferons (IFN-I) limit infection while viral evasion promotes it. To understand how IFN-I and its evasion both control infection outcomes, we used Mx1-cre mice to tag floxed viral genomes in IFN-I responding cells. Epithelial-derived MuHV-4 showed low IFN-I exposure, and neither disrupting viral evasion nor bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 62 publications
4
19
0
Order By: Relevance
“…Invasive virus inoculations are often more pathogenic than mucosal inoculations because they bypass the outer defenses: i.p. MuHV-4 reaches the spleen directly (12), and in this context, IFNAR blockade greatly increases macrophage infection (36), consistent with IFNAR Ϫ/Ϫ mice succumbing more rapidly to i.p. than to i.n.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Invasive virus inoculations are often more pathogenic than mucosal inoculations because they bypass the outer defenses: i.p. MuHV-4 reaches the spleen directly (12), and in this context, IFNAR blockade greatly increases macrophage infection (36), consistent with IFNAR Ϫ/Ϫ mice succumbing more rapidly to i.p. than to i.n.…”
Section: Discussionsupporting
confidence: 57%
“…IFN-I reduces MuHV-4 reactivation from latency in B cells (34), but heightened reactivation normally attenuates infection (35), and the acute phenotypes of IFNAR deficiency are more suggestive of increased lytic replication before B cell colonization. In the spleen, IFN-I restricts mainly macrophage infection (36). Here we show that IFN-I and NK cells are key components of the SSM barrier to MuHV-4 spread.…”
Section: Human Gammaherpesviruses Cause Cancers By Infecting B Cellsmentioning
confidence: 58%
See 1 more Smart Citation
“…, and signaling coreceptors [67,82] Noncoding RNAs (including miRNAs) [41,42,48] Proteins interacting with oriLyts [51] Interferons and other cytokines [30,[32][33][34] Sensors of viral infection [23,83,84] Cell cycle proteins [62,85,86] Proteins regulating apoptosis [87][88][89][90] Transcription factors [91] DNA damage response proteins [5] Proteins involved in epigenetic gene regulation including chromatin assembly, histone modifications[ 3 _ T D $ D I F F ] , and DNA methylation [21][22][23][24][25][26][27][28]63,[92][93][94][95][96][97][98] Autophagy and xenophagy [99][100][101] Ubiquitination and NEDDylation [102][103][104][105] Chaperones [65] Post-translational modification proteins …”
Section: Key Figurementioning
confidence: 99%
“…New data demonstrate cell-type-dependent effects also for type I interferons (IFN-I). Using Mx1-cre mice to tag floxed MHV-68 genomes in IFN-I responding cells, Tan et al [33] demonstrated that the impact of IFN-I on viral replication was strongly cell-type-dependent. In epithelial cells, MHV-68 infection induced only a weak IFN-I response, allowing virus replication.…”
Section: Cytokinesmentioning
confidence: 99%